Water-based phosphorescent pigment composition

By using a combination of specific polymers and glass transition temperatures in fluorescent paints, the problem of traditional fluorescent paints changing the texture of the floor is solved, and the fluorescent effect and ground softness are achieved.

JP7671412B2Active Publication Date: 2025-05-01NIPPON A & L INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024518451
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-11-14
Filing Date
2023-11-14
Publication Date
2025-05-01
Estimated Expiration
2043-11-14

AI Technical Summary

Technical Problem

Fluorescent paints traditionally used on floors such as carpets will change the texture of the floor after application, causing some areas to feel hard and affect the comfort of normal walking.

Method used

A fluorescein combination containing an aqueous medium and a variety of polymers was developed to ensure that the coating maintains a soft texture after drying by adjusting the glass transition temperature and particle size distribution of the polymer.

Benefits of technology

This combination can ensure the softness of the floor material and normal walking comfort while maintaining the fluorescent effect, avoiding the discomfort caused by texture changes in traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671412000001
    Figure 0007671412000001
  • Figure 0007671412000002
    Figure 0007671412000002
  • Figure 0007671412000003
    Figure 0007671412000003
Patent Text Reader

Abstract

An aqueous luminous pigment composition comprising: an aqueous medium; and a polymer and a luminous pigment that are dispersed in the aqueous medium, wherein the polymer is made of a single type or two or more types, and a 0.01 mm-thick film formed from the polymer at 20°C has a haze value conforming to JIS K7136:2000 of 35% or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a water-based phosphorescent pigment composition. [Background technology]

[0002] In emergencies such as major earthquakes and accidents, it may be necessary to evacuate from a room without lighting. In such situations, it is important to have materials that can emit light even in the dark and show evacuation routes or destinations.

[0003] In particular, in order to safely evacuate large numbers of people from places such as hotels, event venues, airplanes, and trains, it is necessary to treat carpets and other flooring materials with phosphorescent materials to prevent confusion during evacuation.

[0004] In consideration of such circumstances, the use of phosphorescent materials using phosphorescent pigments such as phosphorescent fibers, phosphorescent tapes, and phosphorescent paints has been considered. Unlike ordinary fluorescent substances that emit light for a short period of time, phosphorescent pigments emit a long-lasting glow, making them suitable for use in emergencies such as those mentioned above.

[0005] As a paint using a phosphorescent pigment, for example, the water-based emulsion paint disclosed in Patent Document 1 is known. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 6712710 Summary of the Invention [Problem to be solved by the invention]

[0007] However, when paint containing conventional phosphorescent pigments is applied to flooring materials such as carpets to draw a path to an emergency exit, the texture of the painted area changes significantly, making those areas feel hard. Since the painted areas are often indistinguishable under normal circumstances, sudden changes in hardness in different parts of the floor can create an uncomfortable feeling when walking on them under normal circumstances.

[0008] Therefore, an object of the present invention is to provide a composition containing a phosphorescent pigment, which is capable of maintaining the flexibility of a fabric such as a carpet even when the composition is attached to the fabric. [Means for solving the problem]

[0009] The present invention provides the following: [1] A water-based phosphorescent pigment composition comprising an aqueous medium, and a polymer and a phosphorescent pigment dispersed in the aqueous medium, The composition comprises one or more of the above polymers, and a 0.01 mm thick film formed from the above polymer at 20° C. has a haze value of 35% or less in accordance with JIS K7136:2000.

[0010] [2] The aqueous phosphorescent pigment composition according to [1], wherein the polymer is at least one selected from the group consisting of conjugated diene polymers, acrylic polymers, and urethane polymers.

[0011] [3] The aqueous phosphorescent pigment composition according to [1] or [2], wherein the conjugated diene polymer is at least one selected from the group consisting of styrene-butadiene rubber, methyl methacrylate-butadiene rubber, acrylonitrile-butadiene rubber, styrene-butadiene-vinylpyridine rubber, butadiene rubber and natural rubber.

[0012] [4] The aqueous phosphorescent pigment composition according to any one of [1] to [3], wherein the polymer has a glass transition temperature of −40 to 10° C. as measured at a heating rate of 10° C. / min using a differential scanning calorimeter.

[0013] [5] The aqueous phosphorescent pigment composition according to any one of [1] to [4], wherein the phosphorescent pigment is a strontium aluminate compound doped with a lanthanoid rare earth element.

[0014] [6] The water-based phosphorescent pigment composition according to any one of [1] to [5], wherein the phosphorescent pigment has a 90% volume cumulative diameter D90 of 50 μm or less.

[0015] [7] The aqueous phosphorescent pigment composition according to any one of [1] to [6], further comprising at least one selected from the group consisting of a thickener, an anti-drying agent, a pH adjuster, and a preservative.

[0016] [8] Dry weight of fabric: 40 g / m 2 The aqueous phosphorescent pigment composition according to any one of [1] to [7], wherein the bending resistance of a fabric after application, as measured by a handle-o-meter method at 23° C., is less than 300 mN.

[0017] [9] The aqueous phosphorescent pigment composition according to any one of [1] to [8], which is attached to a fabric.

[0018]

[10] The water-based phosphorescent pigment composition according to any one of [1] to [9], which is for inkjet printing. Effect of the Invention

[0019] According to the present invention, there is provided a composition containing a phosphorescent pigment, which is capable of maintaining the flexibility of a fabric such as a carpet even when attached to the fabric. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The water-based luminous pigment composition according to the embodiment is a water-based luminous pigment composition containing an aqueous medium, and a polymer and a luminous pigment dispersed in the aqueous medium, the polymer being composed of one or more types, and a 0.01 mm thick film formed from the polymer at 20°C has a haze value of 35% or less in accordance with JIS K7136:2000.

[0021] The aqueous medium is a medium that holds the polymer and the phosphorescent pigment in the water-based phosphorescent pigment composition, and provides fluidity to the water-based phosphorescent pigment composition.

[0022] The aqueous medium basically contains water such as distilled water, ion-exchanged water, tap water, industrial water, etc., and may further contain water-soluble components (various additives, organic solvents, etc.).

[0023] The polymer is dispersed in the aqueous medium, and may be partially swollen or partially dissolved in the aqueous medium, and typically forms particles (polymer particles) in the aqueous medium.

[0024] The polymer may be provided in the form of a dispersion (emulsion, latex, suspension, etc.) in which the polymer is dispersed in an aqueous medium. The polymer may be one type or two or more types, but two or more types of polymers means that there are two or more types of polymers. When the polymer is provided as a dispersion, in order to provide two or more types of polymers, a dispersion of polymer A (polymer A emulsion), a dispersion of polymer B (polymer B emulsion), and a dispersion of other polymers used as necessary may simply be mixed together.

[0025] The monomer units or structural units constituting each polymer may be of one type or of two or more types. Here, the monomer unit refers to a unit derived from a vinyl compound when a polymer is obtained by vinyl polymerization (e.g., -CH2-CHR 0 - refers to the unit represented by R 0 is a group that forms a side chain of a vinyl compound.) The structural unit means -NHCOO-R 1 -OCONH-R 2 -Units expressed as R 1 is a polyol residue, R 2 means a polyisocyanate residue, which is a structural unit that constitutes polyurethane.) When a polymer is obtained by polycondensation, -RO-R 10 -COO-R11 The unit represented by -O- (R 10 is a polycarboxylic acid residue, R 11 means a polyol residue, which is a structural unit constituting a polyester. 20 -CONH-R 21 The unit expressed as -NH- (R 20 is a polycarboxylic acid residue, R 21 means a polyamine residue, which is a structural unit constituting a polyamide.

[0026] The polymer preferably has a glass transition temperature (hereinafter sometimes abbreviated as "Tg") of -40 to 10°C, measured by a differential scanning calorimeter at a heating rate of 10°C / min. When the Tg is -40°C or higher, for example, when applied to a fabric, a sticky feel (tackiness) can be prevented. On the other hand, when the Tg is 10°C or lower, for example, when applied to a fabric, the entire fabric can be prevented from becoming too hard. The Tg may be -40 to 8°C, -35 to 6°C, or -30 to 6°C.

[0027] When the polymer is provided as a dispersion, the minimum film-forming temperature as specified in JIS K6828-2:2003, i.e., the minimum temperature at which a crack-free uniform film is formed when the polymer dispersion is dried, can be 20°C or less, 15°C or less, 10°C or less, or 5°C or less.

[0028] The haze value of a 0.01 mm thick film formed from a polymer at 20° C., according to JIS K7136:2000, must be 35% or less (that is, 0 to 35%).

[0029] The polymer gel is not particularly limited, but for example, the toluene insoluble content is preferably 40 to 95%. When it is 40% or more, it is possible to easily prevent the fabric from becoming sticky, and when it is 95% or less, it is possible to easily prevent the coating film from becoming brittle and peeling off from the substrate.

[0030] In the course of investigating various water-based phosphorescent pigment compositions, the present inventors have discovered a new finding that when the composition is applied to a fabric such as a carpet, whether or not the flexibility of the fabric can be maintained is related to the haze value, which is an index of transparency. In other words, they have discovered an unexpected relationship in which the maintenance of the flexibility of the fabric is closely related to the haze value, rather than being dependent on the type of polymer or the mechanical properties of the polymer.

[0031] The term "fabric" refers to a material formed into a thin plate shape using a plurality of fibers, and is classified into woven fabric, knitted fabric, lace, felt, nonwoven fabric, and paper according to the manufacturing method.

[0032] Woven fabric means a fabric obtained by crossing warp and weft threads, and knitted fabric means a knitted fabric obtained by making a loop with one or several threads and then passing the next thread through the loop to make a new loop. Lace means a cloth made of one or several threads with a cross-hatch pattern, and felt means a sheet made by compressing animal hair fibers or the like into a thin plate shape. Nonwoven fabric is a sheet in which fibers are intertwined without being woven (excluding paper, felt, and knitted fabric). Nonwoven fabrics include nonwoven fabrics (short fiber nonwoven fabrics) made of short fibers (i.e. staples) and nonwoven fabrics (long fiber nonwoven fabrics) made of long fibers (i.e. filaments). Short fiber nonwoven fabrics generally include carded nonwoven fabrics, airlaid nonwoven fabrics, and wet nonwoven fabrics. Long fiber nonwoven fabrics generally include spunbond nonwoven fabrics and spunlace nonwoven fabrics. Interfiber bonds in short fiber nonwoven fabrics and long fiber nonwoven fabrics include heat, adhesive resins, and interfiber hydrogen bonds, which are the same as interfiber bonds in paper, etc. Although not limited to this, the staple generally has a fiber length of several hundred mm or less.

[0033] The three most typical weaves for textiles are plain weave, twill weave, and satin weave. Among woven fabrics, those generally called carpets (or rugs) include plain weave, tufted weave, Wilton weave, Gobelin weave, Axminster weave, moquette weave, jacquard weave, hand weave, etc.

[0034] The haze value according to JIS K7136:2000 of a 0.01 mm thick film formed at 20°C may be 25% or less, 20% or less, 15% or less, 13% or less, 10% or less, 9% or less, 8% or less, or 6% or less.

[0035] The polymer may be a polymer that gives a value of less than 300 mN when the bending resistance of the solid content of the aqueous phosphorescent pigment composition is measured. The bending resistance is measured by the following method with reference to JIS L1096:2010 (E method, handle-o-meter method). That is, a roll of fabric (cotton twill, vertical density: 114 threads / inch, horizontal density: 54 threads / inch, basis weight: 305.1 g / m 2 ) for a dry weight of 40g / m 2 The aqueous phosphorescent pigment composition is applied to the surface of the rolled fabric (one-sided coating), and dried at 130°C for 10 minutes. A test piece is then cut out in the shape of a strip (24 cm x 1 cm) with the long side in the width direction (TD direction) of the rolled fabric. The test piece is then measured with a 1 cm clearance, a 981 mN measuring weight, and the coated surface facing up. The bending resistance measured by the handle-o-meter method is less than 300 mN for the entire solid content of the aqueous phosphorescent pigment composition.

[0036] The bending resistance value measured by the above-mentioned Handle-O-Meter method may be 220 mN or more and less than 300 mN, 170 mN or more and less than 220 mN, or less than 170 mN.

[0037] The polymer may be at least one selected from the group consisting of a conjugated diene polymer, an acrylic polymer, and a urethane polymer. When the polymer is provided as a dispersion, it is provided as at least one selected from the group consisting of a conjugated diene polymer emulsion, an acrylic polymer emulsion, and a urethane polymer emulsion.

[0038] The conjugated diene polymer may be at least one selected from the group consisting of styrene-butadiene rubber (hereinafter sometimes abbreviated as "SBR", and modified products such as carboxyl-modified are also included in SBR), methyl methacrylate-butadiene rubber (hereinafter sometimes abbreviated as "MBR", and modified products such as carboxyl-modified are also included in MBR), acrylonitrile-butadiene rubber (hereinafter sometimes abbreviated as "NBR", and modified products such as carboxyl-modified, styrene-modified, and (meth)acrylate ester-modified are also included in NBR), styrene-butadiene-vinylpyridine rubber (hereinafter sometimes abbreviated as "VP", and modified products such as carboxyl-modified are also included in VP), butadiene rubber (hereinafter sometimes abbreviated as "BR", and modified products such as carboxyl-modified are also included in BR), and natural rubber (hereinafter sometimes abbreviated as "NR", and polyisoprene is also included in NR).

[0039] When the conjugated diene polymer is provided as a dispersion, it is provided as at least one type selected from the group consisting of a styrene-butadiene rubber emulsion (styrene-butadiene rubber latex), a methyl methacrylate-butadiene rubber emulsion (methyl methacrylate-butadiene rubber emulsion latex), an acrylonitrile-butadiene rubber emulsion (acrylonitrile-butadiene rubber latex), a styrene-butadiene-vinylpyridine rubber emulsion (styrene-butadiene-vinylpyridine rubber latex), a butadiene rubber emulsion (butadiene rubber latex) and a natural rubber emulsion (natural rubber latex).

[0040] Examples of the conjugated diene polymer include copolymers of an aliphatic conjugated diene monomer (e.g., 10 to 80% by mass based on the total monomers), an ethylenically unsaturated carboxylic acid monomer (e.g., 0.5 to 15% by mass based on the total monomers), and other copolymerizable monomers (e.g., 5 to 89.5% by mass based on the total monomers).

[0041] Examples of the aliphatic conjugated diene monomer include 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, substituted linear conjugated pentadiene, substituted and side-chain conjugated hexadienes, etc., and these can be used alone or in combination. In view of the ease of industrial production, availability, and cost, it is particularly preferable to use 1,3-butadiene.

[0042] As the ethylenically unsaturated carboxylic acid monomer, one or more monobasic acids or dibasic acids (anhydrides) such as itaconic acid, acrylic acid, methacrylic acid, crotonic acid, maleic acid, fumaric acid, etc. can be used.

[0043] Examples of other monomers include alkenyl aromatic monomers, vinyl cyanide monomers, unsaturated carboxylic acid alkyl ester monomers, unsaturated monomers containing a hydroxyalkyl group, and unsaturated carboxylic acid amide monomers.

[0044] Examples of alkenyl aromatic monomers include styrene, α-methylstyrene, methyl-α-methylstyrene, vinyltoluene, divinylbenzene, etc. These can be used alone or in combination of two or more. Styrene is particularly preferred from the viewpoints of industrial ease of production, availability, and cost.

[0045] Examples of vinyl cyanide monomers include acrylonitrile, methacrylonitrile, α-chloroacrylonitrile, α-ethylacrylonitrile, etc. These monomers may be used alone or in combination of two or more. In view of ease of industrial production, availability, and cost, it is particularly preferable to use acrylonitrile or methacrylonitrile.

[0046] Examples of the unsaturated carboxylic acid alkyl ester monomer include methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, glycidyl methacrylate, dimethyl fumarate, diethyl fumarate, dimethyl maleate, diethyl maleate, dimethyl itaconate, monomethyl fumarate, monoethyl fumarate, and 2-ethylhexyl acrylate. These can be used alone or in combination of two or more. In view of the ease of industrial production, availability, and cost, it is particularly preferable to use methyl methacrylate.

[0047] Examples of unsaturated monomers containing a hydroxyalkyl group include β-hydroxyethyl acrylate, β-hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, 3-chloro-2-hydroxypropyl methacrylate, di-(ethylene glycol) maleate, di-(ethylene glycol) itaconate, 2-hydroxyethyl maleate, bis(2-hydroxyethyl) maleate, 2-hydroxyethyl methyl fumarate, etc. These may be used alone or in combination of two or more.

[0048] Examples of the unsaturated carboxylic acid amide monomer include acrylamide, methacrylamide, N-methylol acrylamide, N-methylol methacrylamide, N,N-dimethyl acrylamide, etc. These can be used alone or in combination of two or more.

[0049] In addition to the above monomers, any of the monomers used in normal emulsion polymerization, such as ethylene, propylene, vinyl acetate, vinyl propionate, vinyl chloride, and vinylidene chloride, can be used.

[0050] In addition to the above-mentioned conjugated diene polymers, acrylic polymers can be used as the polymer dispersed in the aqueous medium of the water-based phosphorescent pigment composition. Here, the acrylic polymer is a polymer having a (meth)acryloyl group (CH2=CR 30 -CO-, R 30 means a monomer having a hydrogen atom or a methyl group) or a polymer containing a monomer copolymerizable with said monomer as a monomer unit. Here, (meth)acryloyl means acryloyl or methacryloyl, and the same applies to similar compounds.

[0051] The acrylic polymer may be provided as an aqueous dispersion, in which case the aqueous dispersion may be obtained by emulsion polymerization of the raw material monomers. The aqueous dispersion of the acrylic polymer may be a forced emulsion type aqueous dispersion in which a solution of the acrylic polymer in an organic solvent is dispersed in water and at least a part of the organic solvent is removed.

[0052] The acrylic polymer may be an acrylic rubber having elastomer properties, and such an acrylic rubber preferably has a Tg of -40 to 10°C as defined above.

[0053] The acrylic polymer is a copolymer of a low Tg monomer (meaning a monomer that, when homopolymerized, has a Tg of 20° C. or less, preferably 0° C. or less, as defined above) and a high Tg monomer (meaning a monomer that, when homopolymerized, has a Tg of 50° C. or more, as defined above), and an acrylic polymer having a Tg of −40 to 10° C. as a copolymer, as defined above, is preferred. At least one of the low Tg monomer and the high Tg monomer has the above-mentioned (meth)acryloyl group.

[0054] The low Tg monomer includes an acrylic acid ester of a linear or branched non-tertiary alcohol having 1 to 12 carbon atoms, and the number of carbon atoms of the non-tertiary alcohol may be 4 to 12 or 4 to 8. Examples of such non-tertiary alcohol include 1-butanol, 2-butanol, 1-pentanol, 2-pentanol, 3-pentanol, 2-methyl-1-butanol, 3-methyl-1-butanol, 1-hexanol, 2-hexanol, 2-methyl-1-pentanol, 3-methyl-1-pentanol, 2-ethyl-1-butanol, 3,5,5-trimethyl-1-hexanol, 3-heptanol, 1-octanol, 2-octanol, isooctyl alcohol, 2-ethyl-1-hexanol, 1-decanol, 2-propylheptanol, 1-dodecanol, 1-tridecanol, and 1-tetradecanol.

[0055] That is, examples of low Tg monomers include n-butyl acrylate, isobutyl acrylate, hexyl acrylate, 2-ethyl-hexyl acrylate, isooctyl acrylate, caprolactone acrylate, isodecyl acrylate, tridecyl acrylate, lauryl methacrylate, methoxy-polyethylene glycol-monomethacrylate, lauryl acrylate, ethoxy-ethoxyethyl acrylate, and ethoxylated-nonyl acrylate.

[0056] Examples of high Tg monomers include methacrylic acid esters of linear or branched non-tertiary alcohols having 1 to 2 or 6 to 18 carbon atoms, and acrylic acid esters of cyclic non-tertiary alcohols having 6 to 18 carbon atoms.

[0057] That is, examples of high Tg monomers include methyl methacrylate, ethyl methacrylate, stearyl methacrylate, phenyl methacrylate, cyclohexyl methacrylate, isobornyl acrylate, isobornyl methacrylate, benzyl methacrylate, 3,3,5-trimethylcyclohexyl acrylate, cyclohexyl acrylate, and propyl methacrylate.

[0058] In addition to the above, examples of high Tg monomers include styrene, alkylstyrenes (methylstyrene, etc.), (meth)acrylic acid, (meth)acrylamide, N-alkylacrylamides (N-octylacrylamide, etc.), N,N-dialkylacrylamides (N,N-dimethylacrylamide, etc.), (meth)acrylonitrile, etc.

[0059] As the polymer dispersed in the aqueous medium of the water-based phosphorescent pigment composition, in addition to the above-mentioned conjugated diene polymer and acrylic polymer, a urethane polymer can be used.

[0060] The urethane polymer is a polymer having a urethane bond based on the reaction between an isocyanate group and a hydroxyl group, and may have, in addition to the urethane bond, a urea bond based on the reaction between an isocyanate group and an amino group or water, an amide bond based on the reaction between an isocyanate group and a carboxy group, an allophanate group based on the reaction between an isocyanate group and a urethane bond, or a biuret group based on the reaction between an isocyanate group and a urea bond.

[0061] The urethane polymer is obtained by the reaction of polyisocyanate and polyol, and in addition to the polyol, a compound containing active hydrogen other than the polyol (such as polyamine) may be added. In addition, in order to improve water dispersibility, it is possible to use a polyol having a hydrophilic group. Examples of the hydrophilic group include a carboxy group or a salt thereof, a sulfonic acid group or a salt thereof, and a group having a polyoxyethylene skeleton.

[0062] The urethane polymer may be provided as a water dispersion, in which case it may be of the self-emulsifying or forced-emulsifying type.

[0063] The self-emulsifying water dispersion can be obtained by a method of dispersing the polyurethane having the above-mentioned hydrophilic group introduced therein in water (the polymer may be polymerized with an organic solvent such as acetone and then the organic solvent may be removed after the dispersion in water), or by a method of dispersing the isocyanate prepolymer having the above-mentioned hydrophilic group introduced therein in water and extending the chains with a chain extender, or the like.

[0064] A forced emulsification type aqueous dispersion can be obtained by dispersing a polyurethane solution (a solution of solution-polymerized polyurethane or a solution of polyurethane synthesized in a solventless manner in an organic solvent) in water and then removing the organic solvent.

[0065] Examples of polyisocyanates that can be used as a raw material for urethane polymers include aromatic polyisocyanates, araliphatic polyisocyanates, aliphatic polyisocyanates, and alicyclic polyisocyanates.

[0066] Aromatic polyisocyanates include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 2,4-tolylene diisocyanate / 2,6-tolylene diisocyanate mixture, m-xylylene diisocyanate, p-xylylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate / 4,4'-diphenylmethane diisocyanate mixture, and 4,4'-diphenyl ether. Diisocyanate, 2-nitrodiphenyl-4,4'-diisocyanate, 2,2'-diphenylpropane-4,4'-diisocyanate, 3,3'-dimethyldiphenylmethane-4,4'-diisocyanate, 4,4'-diphenylpropane diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, naphthylene-1,4-diisocyanate, naphthylene-1,5-diisocyanate, 3,3'-dimethoxydiphenyl-4,4'-diisocyanate, and the like.

[0067] Examples of the aromatic aliphatic polyisocyanate include 1,3- or 1,4-xylylene diisocyanate or a mixture thereof, 1,3- or 1,4-bis(1-isocyanato-1-methylethyl)benzene or a mixture thereof, ω,ω'-diisocyanato-1,4-diethylbenzene, and the like.

[0068] Examples of the aliphatic polyisocyanate include hexamethylene diisocyanate, tetramethylene diisocyanate, 2-methyl-pentane-1,5-diisocyanate, 3-methyl-pentane-1,5-diisocyanate, lysine diisocyanate, and trioxyethylene diisocyanate.

[0069] Examples of the alicyclic polyisocyanate include isophorone diisocyanate, cyclohexyl diisocyanate, hydrogenated diphenylmethane diisocyanate, norbornane diisocyanate, hydrogenated tolylene diisocyanate, hydrogenated xylene diisocyanate, and hydrogenated tetramethylxylene diisocyanate.

[0070] Examples of polyols that can be used as raw materials for urethane polymers include polyester polyols, polyether polyols, polycarbonate polyols, and polyolefin polyols.

[0071] Examples of polyester polyols include dicarboxylic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalenedicarboxylic acid, succinic acid, tartaric acid, oxalic acid, malonic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, glutaconic acid, azelaic acid, sebacic acid, 1,4-cyclohexyldicarboxylic acid, α-hydromuconic acid, β-hydromuconic acid, α-butyl-α-ethylglutaric acid, α,β-diethylsuccinic acid, maleic acid, and fumaric acid, and anhydrides thereof; and / or ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, and / or ethylene glycol. and one or more of the following polyols: 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 3-methyl-1,5-pentanediol, 3,3-dimethylolheptane, diethylene glycol, dipropylene glycol, neopentyl glycol, cyclohexane-1,4-diol, cyclohexane-1,4-dimethanol, glycerin, trimethylolpropane, diol dimer acid, ethylene oxide or propylene oxide adduct of bisphenol A, bis(β-hydroxyethyl)benzene, and xylylene glycol.

[0072] Examples of polyether polyols include polyether polyols obtained by addition polymerization of alkylene oxides such as ethylene oxide, propylene oxide, butylene oxide, etc., using as an initiator a compound having two active hydrogen groups, such as a low molecular weight polyol or a low molecular weight polyamine such as ethylene diamine, propylene diamine, toluene diamine, metaphenylenediamine, diphenylmethane diamine, xylylene diamine, etc. Examples of polyether polyols include polyether polyols obtained by ring-opening polymerization of cyclic ether monomers such as alkyl glycidyl ethers such as methyl glycidyl ether, aryl glycidyl ethers such as phenyl glycidyl ether, and tetrahydrofuran.

[0073] Examples of polycarbonate polyols include those obtained by a dealcoholization reaction or a dephenolation reaction between one or more low molecular weight polyols and one or more carbonates such as dialkyl carbonates (such as dimethyl carbonate and diethyl carbonate), alkylene carbonates (such as ethylene carbonate and propylene carbonate), diphenyl carbonate, dinaphthyl carbonate, dianthryl carbonate, diphenanthryl carbonate, and diindanyl carbonate.

[0074] Examples of polyolefin polyols include hydroxyl-terminated polybutadiene and its hydrogenated products, and hydroxyl-containing chlorinated polyolefins.

[0075] In the water-based phosphorescent pigment composition, in addition to the polymer, the phosphorescent pigment is dispersed in the water-based medium.

[0076] Luminous pigments, also known as phosphorescent fluorescent materials or phosphorescent materials, are materials that emit light for long periods of time, such as several tens of minutes to several hours, even after the external stimulus has ceased, unlike fluorescent materials, which have an extremely short afterglow time and lose their luminescence when the external stimulus has ceased.

[0077] The phosphorescent pigments are ZnS:Cu (emitting color: green), ZnS:Cu,Mn,Co (emitting color: orange), ZnCdS:Cu (emitting color: yellow to orange), CaS:Eu,Tm (emitting color: red), CaS:Bi (emitting color: purple-blue), CaSrS:Bi (emitting color: blue), SrAl2O4:Eu,Dy (emitting color: green), Sr4Al 14 O 25 :Eu,Dy (luminous color: blue-green), CaAl2O4:Eu,Nd (luminous color: purple), Sr2MgSi2O7:Eu,Dy (luminous color: blue), Y2O2S:Eu,Mg,Ti (luminous color: red), etc.

[0078] As the phosphorescent pigment, a preferred one is one which has a compound represented by MAl2O4 (wherein M is at least one of calcium, strontium, and barium) as a host crystal, to which europium is added as an activator, and to which at least one of cerium, praseodymium, neodymium, samarium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and lutetium is added as a co-activator.

[0079] Among these, a phosphorescent pigment having a compound represented by SrAl2O4 as a host crystal, europium added as an activator, and dysprosium added as a co-activator is useful.

[0080] As the phosphorescent pigment, an acid / phosphate-treated phosphorescent pigment is preferred because of its high water resistance. Such a phosphorescent pigment is produced, for example, by preparing a phosphorescent pigment raw material powder made by doping a strontium aluminate compound with a lanthanoid rare earth element, adding this phosphorescent pigment raw material powder to an aqueous solution containing at least one inorganic acid selected from hydrochloric acid, nitric acid, and sulfuric acid, and at least one phosphate selected from sodium dihydrogen phosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate (at this time, the weight ratio of phosphorescent pigment raw material powder:phosphate is 100:4-14, and the amount of inorganic acid in the aqueous solution is such that the pH of the aqueous solution is 5.0 or less), stirring at a temperature of 20-30°C to perform acid / phosphate treatment, and then washing the obtained phosphorescent pigment with water or neutralizing it with an alkaline aqueous solution and drying (for example, see the description in Japanese Patent No. 5967787).

[0081] The phosphorescent pigment may have a 90% volume cumulative diameter D90 of 50 μm or less. The 90% volume cumulative diameter D90 may be 40 μm or less. The 50% volume cumulative diameter D50 of the phosphorescent pigment may be 20 μm or less, or may be 15 μm or less.

[0082] If the aqueous phosphorescent pigment composition is inkjet printable, it is useful when it is applied to a long piece of fabric, and in such a case, the particle size of the phosphorescent pigment is preferably equal to or smaller than the inner diameter of the nozzle of the inkjet printer. Inkjet printers have various nozzle inner diameters depending on the application, ranging from large ones of 50 μm or more to small ones of 20 μm or less. From the viewpoint of the resolution of the printed matter, it is preferable to make the nozzle inner diameter small, and in such cases, nozzles with inner diameters of 20 μm or less are often used. Therefore, it is preferable that the particle size of the phosphorescent pigment is also 1 μm or less (for example, a phosphorescent pigment with a 50% volume cumulative diameter D50 of 1.0 μm or less). It is preferable that the particle size of the phosphorescent pigment (for example, a 50% volume cumulative diameter D50) is 1 / 10 or less of the inner diameter of the nozzle.

[0083] A useful method for producing a phosphorescent pigment having a 50% volume cumulative diameter D50 of 1.0 μm or less is to use a phosphorescent pigment as a starting material, which contains a mother crystal and an activator and has a 50% volume cumulative diameter D50 of less than 1.0 μm, and to mix the phosphorescent pigment starting material with a predetermined amount of a compound containing an activator for the phosphorescent pigment, and to bake the resulting mixture at a predetermined temperature and in a predetermined atmosphere.

[0084] Specifically, the starting phosphorescent pigment has a composition represented by SrAl2O4:Eu,Dy, or Sr4Al 14 O 25 It has a composition represented by the formula: Eu, Dy. In the mixing step, a compound containing Eu and a compound containing Dy are mixed so that Eu is 0.5 mol % to 4 mol % and Dy is 1 mol % to 8 mol % relative to the starting phosphorescent pigment, and in the firing step, firing is performed at a temperature of 1000°C to 1400°C in a reducing atmosphere (see, for example, the description in JP 2019-210337 A).

[0085] The water-based phosphorescent pigment composition contains the above-mentioned aqueous medium, polymer, and phosphorescent pigment as essential components, and may further contain at least one selected from the group consisting of a thickener (a water-soluble polymer such as sodium polyacrylate, an aqueous dispersion of cellulose nanofiber, etc.), an anti-drying agent (glycerin, diethylene glycol, etc.), a pH adjuster, and a preservative, and in addition to the above, additive components that are soluble or dispersible in the aqueous medium can be added as necessary.

[0086] When the aqueous phosphorescent pigment composition contains a thickener, a drying inhibitor, and a preservative, the polymer content can be, for example, 1 to 20 mass%, 1 to 15 mass%, or 1 to 10 mass%, the phosphorescent pigment can be, for example, 5 to 25 mass%, 5 to 20 mass%, or 5 to 15 mass%, the thickener content can be, for example, 0.1 to 1 mass%, 0.1 to 0.8 mass%, or 0.1 to 0.5 mass%, and the preservative content can be, for example, 0.05 to 0.5 mass%, 0.05 to 0.3 mass%, or 0.05 to 0.2 mass%. When the aqueous phosphorescent pigment composition contains a pH adjuster, the pH adjuster content is preferably such that the pH of the aqueous phosphorescent pigment composition as a whole is weakly alkaline to neutral (for example, pH 7 to 11, pH 7 to 10, or pH 7 to 8). All of these contents are based on the total amount of the aqueous phosphorescent pigment composition.

[0087] The viscosity of the aqueous phosphorescent pigment composition at 23°C can be 1 to 200 mPa s, 1 to 100 mPa s, or 1 to 50 mPa s, when the viscosity is measured 30 seconds after the start of rotation at a rotation speed of 60 rpm using a B-type viscometer (for example, TVB-10 manufactured by Toki Sangyo Co., Ltd.) in accordance with the measurement method of JIS K7117-1.

[0088] The aqueous phosphorescent pigment composition may be produced by mixing a polymer dispersion (polymer emulsion) and a phosphorescent pigment at room temperature (23° C.), for example. When mixing, additives such as a thickener, a drying inhibitor, and a preservative may be added as necessary. EXAMPLES

[0089] The present invention will be described below with reference to examples, but the present invention is not limited to the following examples.

[0090] [Polymer preparation] (Preparation Example 1: Emulsion A) In a pressure-resistant polymerization reactor, 90 parts by mass of polymerization water, 0.16 parts by mass of sodium hydrogen carbonate, 0.6 parts by mass of sodium dodecylbenzenesulfonate, 5.2 parts by mass of styrene, 2.7 parts by mass of 1,3-butadiene, 0.1 parts by mass of methyl methacrylate, 4 parts by mass of cyclohexene, 1.2 parts by mass of acrylic acid, 1 part by mass of hydroxyethyl acrylate, and 0.5 parts by mass of fumaric acid were charged under a nitrogen atmosphere, and stirring was started. 1 part by mass of potassium persulfate was added to raise the temperature inside the reactor to 68°C, and 66.3 parts by mass of styrene, 23 parts by mass of 1,3-butadiene, 1 part by mass of t-dodecyl mercaptan, and 0.5 parts by mass of sodium dodecylbenzenesulfonate were continuously added over 450 minutes. The polymerization was then terminated when the polymerization conversion rate exceeded 98%. Next, the pH of the resulting emulsion was adjusted to 7.0 with an aqueous sodium hydroxide solution, and steam distillation was performed to remove unreacted monomers and other low-boiling compounds, thereby obtaining Emulsion A.

[0091] (Preparation Example 2: Emulsion B) In a pressure-resistant polymerization reactor, 90 parts by mass of polymerization water, 8.0 parts by mass of styrene, 5.0 parts by mass of 1,3-butadiene, 0.5 parts by mass of methyl methacrylate, 1 part by mass of acrylonitrile, 0.5 parts by mass of acrylic acid, 1 part by mass of hydroxyethyl acrylate, 1.5 parts by mass of fumaric acid, 2 parts by mass of cyclohexene, 0.05 parts by mass of t-dodecyl mercaptan, 0.5 parts by mass of sodium hydrogen carbonate, and 0.5 parts by mass of sodium dodecylbenzenesulfonate were charged under a nitrogen atmosphere and stirring was started. 1 part by mass of potassium persulfate was added to raise the temperature inside the reactor to 66 ° C., and 52 parts by mass of styrene, 24 parts by mass of 1,3-butadiene, 4 parts by mass of acrylonitrile, 2.5 parts by mass of methyl methacrylate, and 0.45 parts by mass of t-dodecyl mercaptan were continuously added over 530 minutes. Thereafter, the temperature inside the polymerization reactor was raised to 70°C, and the polymerization was terminated when the polymerization conversion rate exceeded 98%. Next, the pH of the obtained emulsion was adjusted to 7.0 with an aqueous sodium hydroxide solution, and steam distillation was performed to remove unreacted monomers and other low boiling point compounds, thereby obtaining Emulsion B.

[0092] (Preparation Example 3: Emulsion C) In a pressure-resistant polymerization reactor, 120 parts by mass of polymerization water, 6.1 parts by mass of styrene, 4.0 parts by mass of 2-ethylhexyl acrylate, 1.5 parts by mass of itaconic acid, 0.03 parts by mass of ethylene glycol dimethacrylate, and 0.25 parts by mass of sodium dodecylbenzenesulfonate were charged under a nitrogen atmosphere and stirring was started. 1 part by mass of potassium persulfate was added to raise the temperature inside the reactor to 70°C, and 54.1 parts by mass of styrene, 34 parts by mass of 2-ethylhexyl acrylate, and 0.27 parts by mass of ethylene glycol dimethacrylate were continuously added over 300 minutes. The polymerization was then terminated when the polymerization conversion rate exceeded 98%. Next, the pH of the resulting emulsion was adjusted to 7.0 with an aqueous sodium hydroxide solution, and steam distillation was performed to remove unreacted monomers and other low-boiling compounds, thereby obtaining Emulsion C.

[0093] (Preparation Example 4: Emulsion D) In a pressure-resistant polymerization reactor, 120 parts by mass of polymerization water, 5.5 parts by mass of styrene, 4.5 parts by mass of 2-ethylhexyl acrylate, 1.5 parts by mass of itaconic acid, 0.2 parts by mass of ethylene glycol dimethacrylate, and 0.25 parts by mass of sodium dodecylbenzenesulfonate were charged under a nitrogen atmosphere and stirring was started. 1 part by mass of potassium persulfate was added, and the temperature inside the reactor was raised to 70°C, and 49.1 parts by mass of styrene, 37.5 parts by mass of 2-ethylhexyl acrylate, and 1.7 parts by mass of ethylene glycol dimethacrylate were continuously added over 300 minutes. The polymerization was then terminated when the polymerization conversion rate exceeded 98%. Next, the pH of the resulting emulsion was adjusted to 7.0 with an aqueous sodium hydroxide solution, and steam distillation was performed to remove unreacted monomers and other low-boiling compounds, thereby obtaining Emulsion D.

[0094] (Preparation Example 5: Emulsion E) In a pressure-resistant polymerization reactor, 120 parts by mass of polymerization water, 5.2 parts by mass of styrene, 4.7 parts by mass of 2-ethylhexyl acrylate, 1.5 parts by mass of itaconic acid, 0.03 parts by mass of ethylene glycol dimethacrylate, and 0.25 parts by mass of sodium dodecylbenzenesulfonate were charged under a nitrogen atmosphere, and stirring was started. 1 part by mass of potassium persulfate was added, and the temperature inside the reactor was raised to 70°C, and 47 parts by mass of styrene, 41.3 parts by mass of 2-ethylhexyl acrylate, and 0.27 parts by mass of ethylene glycol dimethacrylate were continuously added over 300 minutes. The polymerization was then terminated when the polymerization conversion rate exceeded 98%. Next, the pH of the resulting emulsion was adjusted to 7.0 with an aqueous sodium hydroxide solution, and steam distillation was performed to remove unreacted monomers and other low-boiling compounds, yielding Emulsion E.

[0095] (Preparation Example 6: Emulsion F) In a pressure-resistant polymerization reactor, 90 parts by mass of polymerization water, 6.7 parts by mass of styrene, 6.6 parts by mass of 1,3-butadiene, 0.3 parts by mass of methyl methacrylate, 0.5 parts by mass of acrylonitrile, 1.0 parts by mass of hydroxyethyl acrylate, 0.5 parts by mass of acrylic acid, 1.5 parts by mass of fumaric acid, 2 parts by mass of cyclohexene, 0.3 parts by mass of sodium dodecylbenzenesulfonate, and 0.3 parts by mass of sodium hydrogen carbonate were charged under a nitrogen atmosphere and stirring was started. 1 part by mass of potassium persulfate was added to raise the temperature inside the reactor to 66 ° C., and 40.3 parts by mass of styrene, 37.4 parts by mass of 1,3-butadiene, 2.2 parts by mass of methyl methacrylate, 3 parts by mass of acrylonitrile, and 0.5 parts by mass of t-dodecyl mercaptan were continuously added over 510 minutes. Thereafter, the temperature inside the polymerization reactor was raised to 80° C., and the polymerization was terminated when the polymerization conversion rate exceeded 98%. Next, the pH of the obtained emulsion was adjusted to 7.0 with an aqueous sodium hydroxide solution, and steam distillation was performed to remove unreacted monomers and other low boiling point compounds, thereby obtaining Emulsion F.

[0096] (Preparation Example 7: Emulsion G) In a pressure-resistant polymerization reactor, 95 parts by mass of polymerization water, 7.2 parts by mass of styrene, 2.3 parts by mass of 1,3-butadiene, 1.2 parts by mass of acrylic acid, 0.5 parts by mass of fumaric acid, 2 parts by mass of hydroxyethyl acrylate, 6 parts by mass of cyclohexene, 0.03 parts by mass of t-dodecyl mercaptan, 0.9 parts by mass of sodium dodecylbenzenesulfonate, and 0.3 parts by mass of sodium hydrogen carbonate were charged under a nitrogen atmosphere and stirring was started. 1 part by mass of potassium persulfate was added to raise the temperature inside the reactor to 70°C, and 19.5 parts by mass of styrene, 5.3 parts by mass of 1,3-butadiene, and 0.06 parts by mass of t-dodecyl mercaptan were continuously added over 150 minutes. Immediately after the addition of each monomer and other compounds was completed, 28.0 parts by mass of styrene, 34 parts by mass of 1,3-butadiene, and 0.36 parts by mass of t-dodecyl mercaptan were continuously added over 360 minutes. Thereafter, the temperature inside the polymerization reactor was raised to 85°C, and the polymerization was terminated when the polymerization conversion rate exceeded 98%. Next, the pH of the obtained emulsion was adjusted to 7.0 with an aqueous sodium hydroxide solution, and steam distillation was performed to remove unreacted monomers and other low boiling point compounds, thereby obtaining Emulsion G.

[0097] (Preparation Example 8: Emulsion H) In a pressure-resistant polymerization reactor, 105 parts by mass of polymerization water, 5.2 parts by mass of styrene, 4.6 parts by mass of 2-ethylhexyl acrylate, 1.5 parts by mass of itaconic acid, 0.2 parts by mass of ethylene glycol dimethacrylate, 0.3 parts by mass of sodium dodecylbenzenesulfonate, and 0.3 parts by mass of sodium bicarbonate were charged under a nitrogen atmosphere and stirring was started. 1 part by mass of potassium persulfate was added to raise the temperature inside the reactor to 70°C, and 45.8 parts by mass of styrene, 40.6 parts by mass of 2-ethylhexyl acrylate, 2.1 parts by mass of ethylene glycol dimethacrylate, 0.7 parts by mass of sodium dodecylbenzenesulfonate, and 10 parts by mass of polymerization water were continuously added over 300 minutes. The polymerization was then terminated when the polymerization conversion rate exceeded 98%. Next, the pH of the resulting emulsion was adjusted to 7.0 with an aqueous sodium hydroxide solution, and steam distillation was performed to remove unreacted monomers and other low-boiling compounds, yielding Emulsion H.

[0098] (Preparation Example 9: Emulsion I) In a pressure-resistant polymerization reactor, 0.8 parts by mass of itaconic acid, 0.04 parts by mass of sodium alkyldiphenyletherdisulfonate, 0.24 parts by mass of turpentine oil, 1.4 parts by mass of sodium salt of β-naphthalenesulfonic acid formalin condensate, and 100 parts by mass of polymerization water were charged under a nitrogen atmosphere, stirring was started, and the temperature inside the reactor was raised to 67° C. When the temperature reached 67° C., 0.33 parts by mass of potassium persulfate was added, and immediately after the completion of the addition of potassium persulfate, 9.6 parts by mass of 1,3-butadiene, 14.2 parts by mass of methyl methacrylate, 0.06 parts by mass of t-dodecyl mercaptan, 0.012 parts by mass of turpentine oil, and 0.06 parts by mass of sodium salt of β-naphthalenesulfonic acid formalin condensate were continuously added over 100 minutes. After the addition was completed, the reaction was continued for 80 minutes, and then 20.4 parts by mass of 1,3-butadiene, 31.0 parts by mass of methyl methacrylate, 0.14 parts by mass of t-dodecyl mercaptan, 0.027 parts by mass of turpentine oil, and 0.14 parts by mass of sodium salt of β-naphthalenesulfonic acid formalin condensate were added continuously over 270 minutes. After the addition was completed, stirring was continued for 90 minutes, and then 0.2 parts by mass of itaconic acid, 0.01 parts by mass of turpentine oil, and 0.05 parts by mass of sodium salt of β-naphthalenesulfonic acid formalin condensate were added. Furthermore, 6 parts by mass of 1,3-butadiene, 17.8 parts by mass of methyl methacrylate, 0.1 parts by mass of t-dodecyl mercaptan, 0.05 parts by mass of turpentine oil, and 0.35 parts by mass of sodium salt of β-naphthalenesulfonic acid formalin condensate were added continuously over 120 minutes. The polymerization was then terminated when the polymerization conversion rate reached 98% or more. The pH of the resulting emulsion was then adjusted to 7.0 with potassium hydroxide, and steam distillation was carried out to remove unreacted monomers and other low-boiling compounds, yielding Emulsion I.

[0099] (Preparation Example 10: Emulsion J) In a pressure-resistant reaction vessel, 2 parts by mass of methyl methacrylate, 0.13 parts by mass of sodium dodecylbenzenesulfonate, 0.2 parts by mass of potassium persulfate, and 65 parts by mass of polymerization water were charged under a nitrogen atmosphere, and after thorough stirring, the temperature inside the reactor was raised to 60° C. The reaction was terminated when the polymerization conversion rate reached 99% or more, and the temperature was lowered to 35° C. After the temperature was lowered, 0.15 parts by mass of sodium dodecylbenzenesulfonate was added to obtain a seed latex. In a pressure-resistant reaction vessel, the seed latex obtained under a nitrogen atmosphere was charged with 11 parts by mass of styrene, 14 parts by mass of 1,3-butadiene, 13 parts by mass of methyl methacrylate, 1 part by mass of acrylic acid, 0.5 parts by mass of t-dodecyl mercaptan, and 32 parts by mass of polymerization water, and stirring was started. 0.3 parts by mass of potassium persulfate was added, and the temperature inside the reactor was raised to 60°C, and the reaction was carried out for 305 minutes. Then, 0.5 parts by mass of sodium dodecylbenzenesulfonate was added, and 75 minutes after the addition was completed, 36 parts by mass of styrene, 23 parts by mass of 1,3-butadiene, 0.4 parts by mass of t-dodecyl mercaptan, and 1 part by mass of acrylic acid were continuously added over 270 minutes. After the addition was completed, 0.15 parts by mass of sodium dodecylbenzenesulfonate and 0.05 parts by mass of sodium persulfate were added to the reaction vessel, and the temperature inside the reactor was raised to 70°C. The temperature inside the reactor was maintained at 70°C, and the polymerization was terminated when the polymerization conversion rate exceeded 98%. Next, the pH of the obtained emulsion was adjusted to 7.0 with an aqueous potassium hydroxide solution, and steam distillation was performed to remove unreacted monomers and other low boiling point compounds, thereby obtaining Emulsion J.

[0100] (Preparation Example 11: Emulsion K) In a pressure-resistant polymerization reactor, 130 parts by mass of polymerization water, 1.6 parts by mass of styrene, 4.7 parts by mass of 1,3-butadiene, 6.5 parts by mass of acrylonitrile, 2.5 parts by mass of itaconic acid, 2.0 parts by mass of fumaric acid, 11 parts by mass of cyclohexene, 0.03 parts by mass of t-dodecyl mercaptan, 1.1 parts by mass of sodium dodecylbenzenesulfonate, and 0.5 parts by mass of sodium hydrogen carbonate were charged under a nitrogen atmosphere, and after sufficient stirring, 1.2 parts by mass of potassium persulfate was added and the temperature inside the reactor was raised to 70 ° C. 25.5 parts by mass of styrene, 36.2 parts by mass of 1,3-butadiene, 19 parts by mass of acrylonitrile, 2.0 parts by mass of acrylic acid, and 0.12 parts by mass of t-dodecyl mercaptan were continuously added over 390 minutes. Thereafter, the temperature inside the polymerization reactor was raised to 85°C, and the polymerization was terminated when the polymerization conversion rate exceeded 98%. Next, the pH of the obtained emulsion was adjusted to 7.0 with an aqueous sodium hydroxide solution, and steam distillation was carried out to remove unreacted monomers and other low boiling point compounds, thereby obtaining Emulsion K.

[0101] (Preparation Example 12: Emulsion L) Nalstar SR-110 (carboxy-modified SBR) manufactured by Nippon A&L Co., Ltd. was used as emulsion L.

[0102] (Preparation Example 13: Emulsion M) Cyatex NA-106 (carboxy-modified NBR) manufactured by Nippon A&L Co., Ltd. was used as emulsion M.

[0103] (Preparation Example 14: Emulsion N) In a pressure-resistant polymerization reactor, 57 parts by mass of 1,3-butadiene, 37 parts by mass of acrylonitrile, 6 parts by mass of methacrylic acid, 0.5 parts by mass of t-dodecyl mercaptan, 0.1 parts by mass of sodium dodecylbenzenesulfonate, 0.1 parts by mass of potassium chloride, 0.03 parts by mass of ethylenediaminetetraacetic acid, 0.0004 parts by mass of ferrous sulfate, and 125 parts by mass of polymerization water were charged under a nitrogen atmosphere, and after sufficient stirring, 0.06 parts by mass of potassium persulfate and 0.04 parts by mass of sodium formaldehyde sulfoxylate were added, and the temperature inside the reactor was raised to 30 ° C. Next, when the polymerization conversion rate reached 25%, 0.5 parts by mass of sodium dodecylbenzenesulfonate and 1 part by mass of polymerization water were added. 240 minutes after the addition, the temperature was raised to 45 ° C., and the temperature inside the reaction vessel was maintained at 45 ° C. thereafter. Next, when the polymerization conversion rate reached 60%, 0.8 parts by mass of sodium dodecylbenzenesulfonate and 1.5 parts by mass of polymerization water were added continuously. Next, 0.04 parts by mass of potassium persulfate, 0.02 parts by mass of sodium formaldehyde sulfoxylate, and 0.5 parts by mass of polymerization water were added over 90 minutes. The polymerization conversion rate was checked every 90 minutes, and potassium persulfate, sodium formaldehyde sulfoxylate, and polymerization water were added in the above amounts and times until the polymerization conversion rate reached 95%. After the polymerization conversion rate reached 95%, the temperature inside the reaction vessel was raised to 50°C, and the reaction was stopped when the polymerization conversion rate exceeded 98%. Next, the pH of the obtained emulsion was adjusted to 7.0 with potassium hydroxide, and steam distillation was performed to remove unreacted monomers and other low-boiling point compounds, to obtain Emulsion N.

[0104] (Preparation Example 15: Emulsion O) Nikasol FX-2033 (acrylic emulsion) manufactured by Nippon Carbide Industries Co., Ltd. was used as emulsion O.

[0105] (Preparation Example 16: Emulsion P) In a pressure-resistant polymerization reactor, 90 parts by mass of polymerization water, 6.0 parts by mass of styrene, 4.0 parts by mass of 1,3-butadiene, 1.0 parts by mass of methyl methacrylate, 1.0 parts by mass of hydroxyethyl acrylate, 2.0 parts by mass of fumaric acid, 2 parts by mass of cyclohexene, 0.15 parts by mass of sodium dodecylbenzenesulfonate, and 0.3 parts by mass of sodium bicarbonate were charged under a nitrogen atmosphere and stirring was started. 1 part by mass of potassium persulfate was added and the temperature inside the reactor was raised to 70°C, and 54.0 parts by mass of styrene, 29.0 parts by mass of 1,3-butadiene, 3.0 parts by mass of methyl methacrylate, 0.47 parts by mass of t-dodecyl mercaptan, and 0.1 parts by mass of sodium dodecylbenzenesulfonate were continuously added over 420 minutes. After the addition of each monomer and other compounds was completed, 0.1 parts by mass of t-dodecyl mercaptan was immediately added and reacted for 150 minutes while maintaining the temperature at 70°C. Thereafter, the temperature inside the polymerization reactor was raised to 85°C, and the polymerization was terminated when the polymerization conversion rate exceeded 98%. Next, the pH of the obtained emulsion was adjusted to 7.0 with an aqueous sodium hydroxide solution, and steam distillation was performed to remove unreacted monomers and other low boiling point compounds, thereby obtaining Emulsion P.

[0106] (Preparation Example 17: Emulsion Q) Emulsion Q was obtained by mixing emulsion O and emulsion P in a dry weight ratio of 1:1.

[0107] (Preparation Example 18: Emulsion R) UW-1013D-C1 (urethane dispersion) manufactured by UBE Corporation was used as emulsion R.

[0108] (Preparation Example 19: Emulsion S) Emulsion P and emulsion R were mixed in a dry weight ratio of 1:1 to obtain emulsion S.

[0109] (Preparation Example 20: Emulsion T) Emulsion T was obtained by mixing emulsion O and emulsion R in a dry weight ratio of 1:1.

[0110] For the emulsions obtained in the above Preparation Examples, Tg, gel content (%) and haze value were measured by the following methods.

[0111] [Tg] The emulsion was cast onto a glass plate and dried at 70°C for 4 hours to prepare a film, which was then packed into an aluminum pan and set in a differential scanning calorimeter (DSC7020: Hitachi High-Tech Science Corp.). After cooling to -100°C, the apparatus was heated at a rate of 10°C / min to plot a DSC curve and a DSC differential curve. Tg refers to the intersection of the tangents of the start and maximum inflection points of the heat absorption of the phase change in the DSC curve, which are read, and the tangents of each point are drawn. If there are multiple heat absorption start points, the start and maximum inflection points of the heat absorption of the phase change in the DSC curve are read for each peak having a peak height ratio of 70% or more to the maximum peak height of the DSC differential curve, and the intersection of the tangents of each point is calculated, and the average of these is the Tg value. The peak height refers to the length of the perpendicular line drawn from the peak top of the DSC differential curve to the straight line connecting the start and end points of the heat absorption of the DSC differential curve.

[0112] [Haze value] The emulsion was applied onto a PET film with a thickness of 0.1 mm using a rod bar (#8) and air-dried at 20°C for 10 minutes to obtain a film. The film thickness was 0.01 mm. After leaving the film standing overnight in an environment of 23°C and 50% RH, the haze value (JIS K7136:2000) was measured using a haze meter (HM-150N, manufactured by Murakami Color Research Laboratory Co., Ltd.). This value is H1. As a blank, the haze value (JIS K7136:2000) of a PET film without emulsion coating was also measured in the same manner. This value is H2. The haze value was calculated by subtracting H1 from H2 (blank correction).

[0113] [Preparation of Water-Based Phosphorescent Pigment Composition] The components were mixed at room temperature (23°C) so that the mass percentage relative to the total mass of the composition was as shown in Table 1 below, to obtain a composition. The preservative used was Levanax BX-150, an isothiazolinone preservative manufactured by Shoei Chemical Co., Ltd. The thickener used was sodium polyacrylate (solid content 15±0.5%, pH 9.0±0.5%, B-type viscosity 4000-6000mPa·s). The phosphorescent pigment used was SrAl2O4:Eu,Dy (emission color: green) manufactured by LTI Corporation, with a 90% volume cumulative diameter D90 of 40μm or less and a 50% volume cumulative diameter D50 of 10±4μm.

[0114] [Table 1]

[0115] The composition obtained above and water were stirred to obtain a water-based phosphorescent pigment composition. The amount of water was adjusted so that the total solid content of the water-based phosphorescent pigment composition was 70%. The compositions using emulsions A and B are the water-based phosphorescent pigment compositions of Comparative Examples 1 and 2, and the compositions using emulsions C, D, E, F, G, H, I, J, K, L, M, N, O, P, Q, R, S, and T are the water-based phosphorescent pigment compositions of Examples 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, and 18, respectively.

[0116] [Preparation of fabric coated with water-based phosphorescent pigment composition] The aqueous phosphorescent pigment compositions of Comparative Examples 1-2 and Examples 1-18 were diluted to a total solid content of 50% by mass just before spray coating, stirred, filtered through a 200 mesh filter, and spray-coated onto fabric using a spray gun set SSG-15S-LC manufactured by KINKI. A roll of fabric (manufactured by Shikisen Co., Ltd., cotton twill, with sill) was unwound and cut into pieces (30 cm x 25 cm) measuring 25 cm in the MD direction (length direction) and 30 cm in the TD direction (width direction). The back side of the cut fabric (the outer surface opposite to the inner surface of the winding) was then coated with a 40 g / m2 dry weight. 2The aqueous phosphorescent pigment composition diluted as described above was applied (single-sided coating) so that the thickness became 100 μm, and then dried in a hot air oven at 130° C. for 10 minutes. Immediately after being taken out of the hot air oven, the fabric coated with the water-based phosphorescent pigment composition was sandwiched between 2 cm thick polycarbonate plates while still hot, and the fabric was stretched.

[0117] [Bending resistance measured by handle-o-meter method] A 24cm x 1cm rectangular test piece was cut out from the fabric coated with the water-based phosphorescent pigment composition. The bending resistance was measured by the handle-o-meter method using a No. 226 handle-o-meter manufactured by Yasuda Seiki Seisakusho Co., Ltd., with a clearance of 1cm, a measuring weight of 981mN, and the coated surface facing up. At this time, six test pieces were taken from each piece of fabric, and after obtaining the evaluation value of n6, the highest and lowest values ​​were excluded and the average value was calculated for the remaining four points. Two fabric test pieces were prepared for each emulsion, and the respective average values ​​were further averaged to obtain the Handle-O-Meter measurement value. Specifically, the process is as follows. Taking emulsion A as an example, emulsion A was applied to a fabric to obtain two pieces of applied fabric, A1 and A2, and six pieces of fabric test pieces of the above size were obtained from each of A1 and A2. As a result, a total of 12 pieces of fabric test pieces, A1-1, A1-2, A1-3, A1-4, A1-5, A1-6; A2-1, A2-2, A2-3, A2-4, A2-5, A2-6, were obtained. For A1-1, A1-2, A1-3, A1-4, A1-5 and A1-6, the bending resistance was measured by the handle-ometer method under the above conditions, and the average value (A1-ave) was calculated from the four measured values ​​excluding the maximum and minimum bending resistance values. Similarly, the bending resistance of A2-1, A2-2, A2-3, A2-4, A2-5 and A2-6 was measured by the handle-ometer method under the above conditions, and the average value (A2-ave) was calculated from the four measured values ​​excluding the maximum and minimum bending resistance values. The average value of A1-ave and A2-ave was taken as the bending resistance (mN) of emulsion A measured by the handle-o-meter method.

[0118] [Sensory evaluation] From the same fabric test piece used for the hardness and softness by the handleometer method, a 25 cm × 2 cm test piece for sensory evaluation was obtained. Twenty subjects were divided into four groups of five each, and the test pieces for sensory evaluation were distributed to each group. They were asked to assign four ranks of evaluation scores from the one that felt the hardest (D) to the one that felt the softest (A). The evaluations were set as D < C < B < A from the harder one to the softer one. After tabulation, for each emulsion, the evaluation with the largest number of people was taken as the sensory evaluation of that emulsion. The evaluation of the sensory test followed Table 2 below. It was judged that C to A were hardness values allowable in practical use.

[0119] [Table 2]

[0120] The Tg and haze value of the emulsion, as well as the results of the hardness and softness by the handleometer method and the sensory test evaluation of the aqueous photoluminescent pigment composition, are shown in Table 3. Note that the sensory test data show the ratio of the number of subjects evaluated as A to D.

[0121] [Table 3]

Claims

1. A water-based phosphorescent pigment composition comprising an aqueous medium, one or more polymers dispersed in the aqueous medium, and a phosphorescent pigment having a 90% cumulative volume diameter D90 of 50 μm or less, the polymer is at least one selected from the group consisting of a conjugated diene polymer, an acrylic polymer, and a urethane polymer; The emulsion of the polymer is applied onto a PET film having a thickness of 0.1 mm, air-dried at 20° C. for 10 minutes to give a thickness of 0.01 mm, and allowed to stand overnight in an environment of 23° C. and 50% RH. When the haze value of the film measured in accordance with JIS K7136:2000 is H1, and the haze value of the PET film not coated with the emulsion is measured in accordance with JIS K7136:2000 is H2, the blank-corrected haze value calculated by H1-H2 is 35% or less.

2. 2. The aqueous phosphorescent pigment composition according to claim 1, wherein the conjugated diene polymer is at least one selected from the group consisting of styrene-butadiene rubber, methyl methacrylate-butadiene rubber, acrylonitrile-butadiene rubber, styrene-butadiene-vinylpyridine rubber, butadiene rubber and natural rubber.

3. 2. The water-based phosphorescent pigment composition according to claim 1, wherein the polymer has a glass transition temperature of −40 to 10° C. as measured at a heating rate of 10° C. / min using a differential scanning calorimeter.

4. 2. The water-based phosphorescent pigment composition according to claim 1, wherein the phosphorescent pigment is a strontium aluminate compound doped with a lanthanoid rare earth element.

5. 2. The aqueous phosphorescent pigment composition according to claim 1, further comprising at least one selected from the group consisting of a thickener, a drying inhibitor, a pH adjuster, and a preservative.

6. The fabric has a dry weight of 40 g / m 2 2. The water-based phosphorescent pigment composition according to claim 1, wherein the bending resistance of the coated fabric at 23°C measured by a handle-o-meter method is less than 300 mN.

7. 2. The water-based phosphorescent pigment composition according to claim 1, which is attached to a fabric.

8. The water-based phosphorescent pigment composition according to any one of claims 1 to 7, which is for inkjet printing.

Citation Information

Patent Citations

  • Aqueous ink

    JP2003073599A

  • Copolymer latex, method for producing the same and paper coating composition

    JP2003268019A

  • Water-based fluorescent printing ink and recording method

    JP2006249355A

  • Aqueous coating composition and laminated coating film using the same

    JP2007270094A

  • Fancy coating film-forming composition, and method for finishing fancy coating

    JP2008121006A